PERAN NADZIR DALAM PENGEMBANGAN WAKAF - Kasdi, Abdurrahman (UIN Sunan Kudus, 2014)
Existence nadzir very important in maintaining and managing the waqf.According to Law No. 41 of 2004 amid Endowments, Nadzir divided intothree, namely: nadzir individuals, organizations and nadzir nadzir legalentity. Nadzir efforts in developing endowment assets ie the memproduktifkanwaqf. In addition, no less important is the security of property assets donatedto charitable status is not contested by the parties are not responsible. There areseveral things that must be done by the Inspectors, such as: first, immediatelymake available the certificate of land ownership (if the endowment assets, suchas land). Second, advocates of endowment assets, which are still disputed.Third, strengthening the productive waqf property. Nadzir have a central rolein the management of waqf in general. Therefore, the existence and quality ofhuman resources should nadzir exactly observed. Nadzir (whether individuals,organizations and legal entities) must be made up of people who are honorable,honest, well-behaved, experienced, mastered the science of administrationand finance necessary to carry out its duties in accordance with the type ofownership and purpose. In general, the management of waqf can be directedand built optimally, when nadzirnya trust (trustworthy) and professional.